Prescription of Combined HRT in Non- Hysterectomised Women in General Practice - Stuart, Ellen (Trinity Student Medical Journal, 2004)
Objective: The prescribing practice of combined hormone replacement therapy (HRT) medication in non-hysterectomised women in one Dublin general practice (GP) surgery from 1996 to 2003 was investigated in this study. The aim of the study was to explore whether Irish GP prescribing practice reflected the Irish College of General Practitioners (ICGP) guidelines from the Saffron Initiative (referenced in the Monthly Index of Medical Specialties (MIMS)) which guide the timing of prescription of combined cyclical HRT (CYHRT) versus continuous combined HRT (CCHRT) according to age. Methods: Using the GP Clinical Computer program in the practice, the number of prescriptions of combined HRT, the age of women at the time of their first prescription, the average age of prescription of CYHRT versus CCHRT and the percentage of women older or younger than the recommended ages for each type of combined HRT were calculated. Results: A total of 90 prescriptions for CYHRT were identified during the time period 1996 to 2003. The age range of the women was 40 to 57 years with an average age of prescription of 49.73 years. It was found that 24% of the prescriptions made were to women above the recommended cut-off point of 51 years. A total of 60 prescriptions for CCHRT were found for the time period 1996 to 2003. The age range of these women was 44 to 61 years with the average age of prescription being 51.33 years, of whom 32% were below 51 years. Conclusion: The age cut-off point of 51 years applied to most patients in terms of prescribing CYHRT versus CCHRT. It did not apply to all patients though and this fact is in keeping with updated ICGP guidelines from the Saffron Initiative. This emphasises the importance of evaluating each patient on an individual basis.